Effect of propagation of a reflected shock wave on a pressure field when a detonation wave reflects on an end wall of a tube with opened or closed ignition end - Shinichi MAEDA; Yosuke OIKAWA; Ryusuke HOSHINO; Tetsuro OBARA (Nihon Kikai Gakkai ronbunshu, 2017)
A detonation wave propagating in a straight tube (detonation tube) was reflected off the end wall of the tube, and the pressure profile produced by the propagation of the reflected shock wave was experimentally investigated. The detonation wave was initiated at the opposite end of the reflection end, and two ignition conditions were tested. First, ignition at the closed end of the tube (called as “closed ignition end condition”), where the fluid motion was negligible, was evaluated. Second, ignition at the open end of the tube (called as “opened ignition end condition”), where the burned gas flowed toward the vacuum tank attached to the detonation tube, was evaluated. Karnesky et al. (2013) suggested the empirical model in order to represent the pressure profile near the reflection end in the closed ignition end condition. In this paper, the empirical model of Karnesky et al. was modified in order to represent the pressure profile in the opened ignition end condition, and the effect of two ignition conditions on the pressure profiles was discussed. In these models, the pressure profile at the reflection end was empirically formulated by using two empirical parameters, and a uniform pressure distribution between the reflected shock wave and the reflection end was assumed. In this paper, the empirical parameters were normalized by the characteristic parameters for the propagating reflected shock wave. These parameters expressed the conditions of the combustible mixture and the length of the detonation tube. In the opened ignition end condition, the model well represented the measured pressure profile created by the propagating detonation wave and reflected shock wave in the entire length of the detonation tube because the rarefaction wave existed in the entire region behind the detonation wave, and the pressure behind the reflected shock wave had an approximately uniform distribution. Conversely, the model was applicable for a limited duration for the closed ignition end condition because a pressure gradient gradually developed behind the reflected shock wave when the reflected shock wave began to propagate in the plateau region behind the rarefaction wave.